Imaging as Praxis: Cataloging, Housing, and Installing Lele Saveri's The Newsstand. Issue 2 (June 2018) - Lutek, Tasha
In 2013, The Newsstand, a pop-up space featuring hundreds of zines and art objects, was installed in a Brooklyn, New York, subway station. The space was designed to be a site of collaboration and inspiration for artists. Even though the intention was not for it to be an artwork, two years later the Museum of Modern Art (MoMA) re-created and exhibited The Newsstand in its galleries. To activate the installation, visitors were invited to engage with the space and read the zines contained inside. At the close of the exhibition, the work entered MoMA's collection and shortly after was lent to the Fondation Louis Vuitton (FLV). The volume of material and interactive qualities of The Newsstand present unique challenges for collection staff. Using two museum installations as departure points, this is a case study outlining the strategies employed for cataloging, housing, and installing this complex work, focusing on how imaging played an essential role in making sense of the transition from nonart status to collection object.